Miscellaneous Sumerian Hymns - Sjöberg, Å. W.
SRT 12 and CBS 14074; UM 29-15-6; UM 29-16-21 and ISET I 98f.; CBS 2135 + 19829 and N 3324; CBS 8084 and UM 29-15-58; PBS 10/4 No. 7 and CBS 7140; UM 29-16-3.